Two-stage low-carbon optimal dispatch of the power system considering demand response to defend large uncertainties and risks - Cai, Linjun; Xie, Dongliang; Xue, Feng; Zhang, Huilin (Frontiers in Energy Research, 2024)
To advance new energy consumption and diminish carbon emissions, while effectively addressing risks brought by renewable energy and load uncertainty, a two-phase low-carbon dispatch model is proposed herein, considering demand response alongside the varied uncertainties in wind power, photovoltaic as well as load fluctuation. Firstly, uncertainty scenario set undergoes generation via Latin hypercubic sampling. Following this, heuristic synchronous backpropagation method for scene reduction is used to obtain typical scenarios along with their respective probabilities. Secondly, the first stage optimization model is proposed with the aim of maximizing energy utilization benefits and acquiring the correlated demand response strategy. Thirdly, a joint green certificate transaction as well as carbon trading mechanism is established, that is composed of stepwise green certificate transaction and time-shared stepwise carbon trading. This model serves to optimize the output of second stage units under typical scenarios, aiming to minimize comprehensive operating costs. Eventually, the simulation results test and verify superiority of the proposed scheduling approach on reducing economic costs and carbon dioxide, ensuring both economic efficiency and environmental preservation within the power system.